2017
DOI: 10.1016/j.bbagen.2016.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the role of fiber length on phagocytosis and inflammatory response by alveolar macrophages

Abstract: Background In the lung, macrophages attempt to engulf inhaled high aspect ratio pathogenic materials, secreting inflammatory molecules in the process. The inability of macrophages to remove these materials leads to chronic inflammation and disease. How the biophysical and biochemical mechanisms of these effects are influenced by fiber length remains undetermined. This study evaluates the role of fiber length on phagocytosis and molecular inflammatory responses to non-cytotoxic fibers, enabling development of q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 60 publications
1
44
0
Order By: Relevance
“…The difference in size of the ABs located along the fibre and that of the bulbous ABs at the tip of the fibre has never been considered to date. Time-lapse video microscopy of macrophage-asbestos fibre-binding events [62,63] showed that the macrophages try to internalise the long fibres by preferentially starting from their terminations. Consequently, this portion of the fibre is subject to repeated coatings, leading to increased thickness.…”
Section: New Insights In the Mechanism Of Formation Of Absmentioning
confidence: 99%
“…The difference in size of the ABs located along the fibre and that of the bulbous ABs at the tip of the fibre has never been considered to date. Time-lapse video microscopy of macrophage-asbestos fibre-binding events [62,63] showed that the macrophages try to internalise the long fibres by preferentially starting from their terminations. Consequently, this portion of the fibre is subject to repeated coatings, leading to increased thickness.…”
Section: New Insights In the Mechanism Of Formation Of Absmentioning
confidence: 99%
“…Thin and long fibers may induce a state of chronic inflammation in target tissues, due to their ability to persist for a very long time in human body. Indeed as macrophages may reach 10-20 µm diameter, fibers longer 20 µm cannot be completely phagocytosed, thus leading to incomplete or 'frustrated' phagocytosis, characterized by the prolonged release of pro-inflammatory cytokines by activated macrophages [9]. Asbestos-induced chronic inflammation may activate multiple signaling cascades involved in cell proliferation and survival, including the epidermal growth factor receptor (EGFR) pathway [10].…”
Section: Asbestos Carcinogenesismentioning
confidence: 99%
“…For example, in one study, gold nanorods were internalized by macrophages at greater levels than nanospheres owing to preferential uptake of the former via micropinocytosis . In a separate study, glass rods were used as a tool to assess shape dependence by incubating rods of varying lengths with macrophages . Short rods were more rapidly taken up than longer rods, but interestingly, the longer rods, while not readily phagocytosed, induced greater levels of the inflammatory signals IL‐1α and TNF‐α .…”
Section: Understanding Intrinsic Immunogenicity Of Biomaterials Delivementioning
confidence: 99%
“…In a separate study, glass rods were used as a tool to assess shape dependence by incubating rods of varying lengths with macrophages . Short rods were more rapidly taken up than longer rods, but interestingly, the longer rods, while not readily phagocytosed, induced greater levels of the inflammatory signals IL‐1α and TNF‐α . This inflammatory response was attributed to “frustrated” phagocytic interactions, a phenomenon that occurs when cells are unable to phagocytose larger‐scale objects.…”
Section: Understanding Intrinsic Immunogenicity Of Biomaterials Delivementioning
confidence: 99%
See 1 more Smart Citation